2014
DOI: 10.1016/j.neuropharm.2013.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-mediated neuroprotection in in vitro models of excitotoxicity involves astrocytic activation and the inhibition of MAP kinase signalling pathways

Abstract: It is well established that immunosurveillance is active in the CNS and plays a key role in several CNS disorders but the exact role of immune cells remains elusive. Thus, in the present study we investigated whether lymphocytes are protective/detrimental in in vitro models of excitotoxicty. Kainate (KA)-induced neuronal death was significantly reduced following exposure to mixed lymphocytes or purified T lymphocytes containing either activated or non-activated T-lymphocytes. Conditioned media from lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 84 publications
3
18
0
1
Order By: Relevance
“…Next splenocyte-induced demyelination was examined in these organotypic cerebellar slice cultures. We have recently shown that naïve cells isolated from peripheral lymph nodes of wild-type mice are not detrimental to organotypic hippocampal slice cultures, and indeed are neuroprotective against toxicity induced by kainate- and oxygen-glucose deprivation [33]. Accordingly, naïve-splenocytes did not induce any significant change in MBP staining when applied to organotypic cerebellar slice cultures ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 86%
“…Next splenocyte-induced demyelination was examined in these organotypic cerebellar slice cultures. We have recently shown that naïve cells isolated from peripheral lymph nodes of wild-type mice are not detrimental to organotypic hippocampal slice cultures, and indeed are neuroprotective against toxicity induced by kainate- and oxygen-glucose deprivation [33]. Accordingly, naïve-splenocytes did not induce any significant change in MBP staining when applied to organotypic cerebellar slice cultures ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 86%
“…Changes occurring in most neurodegenerative conditions were the high expression of a group of transcripts encoding the lysososmal cathepsin inhibitor Cystatin F (Cst7) (Ma et al, 2011), osteopontin (Spp1), an opsonin for cell debris (Shin et al, 2011), and cholesterol 25-hydroxylase (Ch25h) that, through its product, 25-hydroxycholesterol, activates the LXR pathway and promotes ROS production and inflammation (Jang et al, 2016). Underexpression of neuroprotective (Clec4a1, Il16) (Flytzani et al, 2013, Shrestha et al, 2014 and anti-inflammatory (Klf2, Gramd4, Ddit4, Pirb, Tsc22d3) (Roberts et al, 2017, Ip et al, 2017, Kimura et al, 2015, Zhang et al, 2005, Berrebi et al, 2003 transcripts was observed in ALSP and at least three other conditions ( Fig. 5H).…”
Section: Gene Expression Changes In Csf1r +/-Microglia Suggest a Malamentioning
confidence: 99%
“…Nonetheless, their infiltration presumably protects neurons by activating astroglial responses and inhibiting death‐triggering mechanisms such as those driven by p38 (Shrestha et al . ). Infiltrated T cells also assist in tissue recovery after injury.…”
Section: Neuroinflammationmentioning
confidence: 97%
“…In this transient phase termed 'acute phase response' (Anthony et al 2012), immune cells infiltrate into the brain parenchyma, causing further disruption of BBB stability. Nonetheless, their infiltration presumably protects neurons by activating astroglial responses and inhibiting death-triggering mechanisms such as those driven by p38 (Shrestha et al 2014). Infiltrated T cells also assist in tissue recovery after injury.…”
Section: Neuroinflammationmentioning
confidence: 99%